Educate Some to Represent Many? Education and Female Political Representation in Europe - Luna Bellani; Marisa Hidalgo-Hidalgo (Institute of Labor Economics (IZA), 2023)
Gender disparity is present in many aspects of life, especially in politics. This paper provides new evidence on the impact of women's education on political representation focusing on several European countries. We combine multi-country data from the Gender Statistics Database of the European Institute for Gender Equality (EIGE) and from the European Social Survey (ESS). We find increased female education significantly raises the percentage of women being elected to regional parliaments. We then explore possible channels at the individual level and find education increases women's interest in politics and induces more egalitarian views about gender roles in society among women, although it fails to do so among men.
Keywords: H52; I21; I23; J24; J31; 330; education; female political participation; compulsory schooling reforms; ESS